Pengaruh Brand Attachment, Desain Visual, dan Iklan Media Sosial terhadap Keputusan Pembelian untuk Melakukan Top-Up dalam Game Love and Deepspace pada Pemain di Indonesia - Bagie, Cut Nova Melvira; Nugraha, Muhammad Hadi Maulidin (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
Love and Deepspace is an interactive mobile game in the visual novel genre that has quickly gained significant attention, particularly among teenagers and young adults. A considerable number of users are also involved in purchasing virtual items offered within the game. The primary objective of this study is to determine whether external factors such as brand attachment, visual design, and social media advertising influence users’ interest in purchasing in-game products. Utilizing IBM SPSS version 22, this study employs quantitative analysis methods, with data collected from 96 participants who completed a questionnaire distributed through various social media platforms, including WhatsApp, Twitter, and Facebook. The sampling technique used is Non-probability Sampling with a Purposive Sampling method. A series of tests, including validity and reliability testing, as well as statistical analysis and coefficient of determination, were conducted to analyze the data. The findings indicate that the decision to purchase virtual items (top-up) is positively and significantly influenced by the variables of brand attachment, visual design, and social media advertising. The results of the study show that the decision to purchase virtual goods (top-up) is positively and significantly influenced by the variables of brand attachment, visual design, and social media advertising. Partially, brand attachment (the player's emotional attachment to the game's characters and elements), visual design (iconic characters, eye-catching colors, and funny visual elements), and social media advertising (interactive, informative, relevant, and entertaining) all have a significant influence on purchasing decisions. Simultaneously, these three independent variables together have a positive and significant effect on purchasing decisions in the Love and Deepspace game. This suggests that these factors are important elements that collectively influence consumer behavior in making top-up purchases.